Peran Moderasi Mekanisme Corporate Governance pada Pengaruh Karakteristik Perusahaan dan Financial Distress Terhadap Kualitas Pelaporan Keuangan - Putri, Cut Widy Aulia; Amri, Abrar; Risnafitri, Hafizhah; Mahdani, Rimal; Firman Hastuti, Cut Sri (Akbis: Media Riset Akuntansi dan Bisnis, 2024)
The purpose of this study is to analyze the influence of firm characteristics and financial distress on the quality of financial reporting, along with the moderation role of corporate governance mechanisms on the relation of firm characteristics and financial reporting quality, and the moderation role of corporate governance mechanisms on the relation of financial distress and financial reporting quality of property and real estate companies listed on the Indonesia Stock Exchange from 2013 to 2017. Total observations on this study were 192. Datas were obtained from annual reports and were analyzed with SEM-PLS using WarpPLS. This study found that (1) firm characteristics have significant impact on financial reporting quality, (2) financial distress has significant impact on financial reporting quality, (3) corporate governance mechanisms moderate the relation of firm characteristics and financial reporting quality, (4) corporate governance mechanisms moderate the relation of financial distress and financial reporting quality.